"Rytuały rodzinne'. Wobec śmierci w filmie - Kulig, Agnieszka (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2012)
In the article Family rituals in the face of death the author analyzes fi lms from the perspective of the experience of a family confronted with death. The author is interestedin what family rituals are still used at this time and what actions have been abandoned.The presented fi lms demonstrate fascination with the topic of death, which is present in every culture with different intensity, by means of various descriptions which are attractive because they are fi lled with the richness of symbols. The majority of these films emphasize a shift in the discourse about death in social space towards an individual subject. The author wanted to observe and show the moment when the community experience of death and mourning was given up and the ritual passed into the hands of specialized institutions.